Membangun Kemandirian Pembiayaan Pendidikan di Pondok Pesantren Mambaul Ulum Sukowono Jember - Hermawan, Dani; Nistiyanah, Nita; Agustin, Nadilla Aleyda Maqhfira; Rohim, Faidhur (Akhlaqul Karimah: Jurnal Pendidikan Agama Islam, 2025)
Education financing is very important and cannot be separated from the world of education because education financing is the main factor that supports the implementation of education. However, education costs cannot always be met due to limited funds, dependence on government funds or other things, therefore it is important for educational institutions to have private funds to support education financing. This research aims to determine efforts to build independence in educational financing and students' perceptions about building independence in educational financing at the Mambaul Ulum Sukowono Jember Islamic boarding school. This research uses a mixed method type of sequential exploratory design, namely research using qualitative methods as main data and quantitative methods as supporting data. In this research, data was obtained through two sources, namely qualitative through observation, interviews and documentation. Meanwhile, quantitative through questionnaire surveys. The results of the research in the form of efforts to build financial independence were the establishment of the Al-Mubarok Islamic boarding school cooperative business and BMT Maslahah Lil Ummah. Meanwhile, the perception of students regarding building independence in financing their education is that 56% agree because with the independence of Islamic boarding schools they have independence in financing education.